Les - konstrukcijsko gradivo v sodobni arhitekturi - Zbašnik-Senegačnik, Martina (Les (Ljubljana), 1998)
In the last decades, when our environment has become increasingly polluted, natural building materials that do not have negative effect on the environment and human begins have been more and more appreciated. Wood as a building material has already regain its constructional function that it once had in the building profession. In the article, some constructional systems in use today for wooden buildings have been shown.
Keywords: civil engineering; gradbeništvo; les; konstrukcije